Global and population-specific association of MTHFR polymorphisms with preterm birth risk: a consolidated analysis of 44 studies - Maryam Vafapour; Hanieh Talebi; Mahsa Danaei; Maryam Yeganegi; Sepideh Azizi; Seyed Alireza Dastgheib; Reza Bahrami; Melina Pourkazemi; Fatemeh Jayervand; Amirhossein Shahbazi; Heewa Rashnavadi; Ali Masoudi; et al. (BMC Pregnancy and Childbirth)
Abstract Background This study investigates the relationship between polymorphisms in the MTHFR gene and the risk of preterm birth (PTB). Methods A comprehensive literature review was conducted using databases such as PubMed, Web of Science, and CNKI, with the search finalized on January 1, 2025. The review specifically targeted studies published prior to this date, utilizing relevant keywords and MeSH terms associated with PTB and genetic factors. Inclusion criteria encompassed original case-control, longitudinal, or cohort studies, with no limitations on language or publication date. Associations were quantified using odds ratios (ORs) and 95% confidence intervals (CIs) via Comprehensive Meta-Analysis software. Results The analysis included 44 case-control studies comprising 7,384 cases and 51,449 controls, extracted from 28 publications in both English and Chinese. Among these studies, 29 focused on the MTHFR C677T polymorphism, while 15 examined the MTHFR A1298C variant. Pooled results demonstrated a significant association between the MTHFR C677T polymorphism and PTB under five genetic models: allele (C vs. T; OR = 1.303, 95% CI 1.151–1.475, p ≤ 0.001), homozygote (CC vs. AA; OR = 1.494, 95% CI 1.212–1.842, p ≤ 0.001), heterozygote (CT vs. AA; OR = 1.303, 95% CI 1.119–1.516, p = 0.001), dominant (CC + CT vs. AA; OR = 1.341, 95% CI 1.161–1.548, p ≤ 0.001), and recessive (CC vs. CT + AA; OR = 1.340, 95% CI 1.119–1.604, p = 0.001). Subgroup analyses indicated significant associations in Asian populations, particularly in studies conducted in China and India, while no significant correlations were found in Caucasian populations, including those from Austria. Moreover, the MTHFR A1298C polymorphism did not demonstrate a significant relationship with PTB risk across the studied ethnicities. Conclusions The findings indicate a significant association between the MTHFR C677T polymorphism and PTB risk, particularly in Asian and Indian populations, while no significant associations were identified in Caucasian groups. Conversely, the MTHFR A1298C polymorphism appeared to have a negligible impact on PTB risk, underscoring the importance of considering population-specific factors in understanding the genetic epidemiology of PTB.